LOCAL BORROWING AS A TOOL FOR THE DEVELOPMENT OF TERRITORIAL COMMUNITIES (World of finance, 2022)
Introduction. At the present stage of development of Ukraine’s economy there is a problem of low level of capital expenditures of local budgets. Local borrowing can be an alternative source of financial resources for local budgets. The issue of increasing local borrowing must be considered not only in the context of their effective use, but also the increase of local debt.The purpose of the article is to research and generalizate the theoretical foundations of local borrowing as a tool for the development of territorial communities.Methods. In the study of the theoretical foundations of local borrowing, such general scientific methods as analysis, synthesis, induction, deduction, abstraction, generalization were used.Results. The article clarifies the economic content of local borrowing and the peculiarities of their implementation in Ukraine, identified shortcomings in the legislation. A study of the forms of local borrowing and their advantages and disadvantages. The classification of local borrowings was carried out, which allowed to deepen their essence.Conclusions. Imperfect legal regulation of local borrowing reduces their role in ensuring investment development of communities. The implementation of local borrowing requires a balanced debt policy.